Oracle SOA suite developer's guide : design and build service-oriented architecture solutions with the Oracle SOA Suite 10gR3 - Wright, Matt, 1980-; Reynolds, Antony (From technologies to solutions., 2009)
"We are moving towards a standards-based Service-Oriented Architecture (SOA), where IT infrastructure is continuously adapted to keep up with the pace of business change. Oracle is at the forefront of this vision, with the Oracle SOA Suite providing the most comprehensive, proven, and integrated tool kit for building SOA based applications"--Resource description page